Stem cell research: toward greater unity in Europe? - Druml, Christiane (Cell, 2009)
There are four major positions on human embryonic stem cell research in the different member states of the European Union, ranging from permissive to very restrictive. This reflects the diversity of research systems within Europe and poses a challenge to developing a common European research policy.